The Transformation of Profane-Sacred Values: A Case Study of Sacred Water at Jagabayan Mosque in Cirebon - Maula, Merdita Rizqia Nikma (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Abstract The kliwonan tradition at Jagabayan Mosque is a tradition that is familiar to the surrounding community. The tradition is connected to the sacred water in the mosque well which is considered sacred by the community. Water as something classified as a profane form has been transformed into a sacred one in the view of the community. This is in line with Mircea Eliade's theory about the transformation of profane into sacred. Thus, this research aims to examine the transformation of value from profane to sacred through Eliade's sacred-profane theory. Furthermore, it will examine the implications of these value changes on people's social actions. This research is a qualitative type with data collection methods through observation, interviews and documentation. The main data source in this research is the kliwonan tradition carried out by the community at Jagabayan Mosque itself, while other supporting data is taken from references that support the research data. The data set will then be processed using the descriptive-analytical method. The results show that the change in the profane value of the water to sacred is due to the attribution of the well as a source of water to the sacred entity of the guardian who used to make it. While the implications resulting from it are the creation of the kliwonan tradition itself and the finding of a special attitude by the community towards the water entity that is considered sacred. Abstrak Tradisi kliwonan di Masjid Jagabayan merupakan tradisi yang sudah tidak asing lagi bagi masyarakat sekitarnya. Tradisi tersebut terhubung dengan air keramat di sumur masjid yang dinilai sakral oleh masyarakat. Air sebagai sesuatu yang tergolong wujud profan telah dialih wujudkan menjadi yang sakral dalam pandangan masyarakat. Hal ini selaras dengan teori Mircea Eliade soal perubahan wujud profan menjadi sakral. Maka, penelitian ini bertujuan untuk menelisik transformasi nilai dari yang profan menjadi sakral melalui teori sakral-profan eliade. Selanjutnya, akan dilakukan telaah pada implikasi perubahan nilai tersebut pada tindakan sosial masyarakat. Penelitian ini berjenis kualitatif dengan metode pengumpulan data melalui observasi, wawancara dan dokumentasi. Sumber data utama pada penelitian ini adalah tradisi kliwonan yang dilakukan masyarakat di Masjid Jagabayan itu sendiri, sedangkan data pendukung lain diambil dari referensi yang mendukung data penelitian. Kumpulan data kemudian akan diolah menggunakan metode deskriptif-analitis. Hasil penelitian menunjukkan bahwa perubahan nilai profan air tersebut menjadi sakral disebabkan oleh penyandaran sumur sebagai sumber air pada entitas sakral wali yang dulu membuatnya. Sedangkan implikasi yang dihasilkan darinya adalah terciptanya tradisi kliwonan itu sendiri dan temuan sikap yang spesial oleh masyarakat pada entitas air yang dianggap sakral tersebut.